Biochemical changes in the brain of hemiplegic migraine patients measured with 7 tesla 1H-MRS. (October 2014) - Zielman, R; Teeuwisse, WM; Bakels, F; Van der Grond, J; Webb, A; van Buchem, MA; Ferrari, MD; Kruit, MC; Terwindt, GM
Aim: The aim of this study was to assess biochemical changes in the brain of patients with hemiplegic migraine in between attacks. Methods: Eighteen patients with hemiplegic migraine (M:F, 7:11; age 38 ± 14 years) of whom eight had a known familial hemiplegic migraine (FHM) mutation (five in the CACNA1A gene (FHM1), three in the ATP1A2 gene (FHM2)) and 19 age- and sex-matched healthy controls (M:F, 7:12; mean age 38 ± 12 years) were studied. We used single-voxel 7 tesla 1 H-MRS (STEAM, TR/TM/TE = 2000/19/21 ms) to investigate four brain regions in between attacks: cerebellum, hypothalamus, occipital lobe, and pons. Results: Patients with hemiplegic migraine showed a significantly lower total N-acetylaspartate/total creatine ratio (tNAA/tCre) in the cerebellum (median 0.73, range 0.59–1.03) than healthy controls (median 0.79, range (0.67–0.95); p = 0.02). In FHM1 patients with a CACNA1A mutation, the tNAA/tCre was lowest. Discussion: We found a decreased cerebellar tNAA/tCre ratio that might serve as an early biomarker for neuronal dysfunction and/or loss. This is the first high-spectral resolution 7 tesla 1 H-MRS study of interictal biochemical brain changes in hemiplegic migraine patients.